Communication Patterns and Media Technology Role in Organization and Society During Pandemic - Putri, Andhita Vidya; Irwansyah, Irwansyah (The Journal of Society and Media, 2020)
The covid-19 pandemic as the background of the Work From Home (WFH) policy is believed to have increased significant participation in communication technology and changed communication patterns. The research aims to know the implementation of WFH during the pandemic, the use of communication technology, the communication patterns during WFH that have changed from face-to-face to Computer-Mediated Communication (CMC), and the essential factors for the success of WFH. A qualitative method with a descriptive case study approach and a semi-structured interview technique is used. The theory is media richness theory. The results showed that WFH offered advantages and disadvantages for employees and organizations. WFH featured various types of technology/media, from lean to rich. Communication technology plays an essential role during WFH, which causes changes in communication patterns. Different technologies/media vary in their ability to reproduce messages. During WFH, CMC creates a different climate than face-to-face communication because CMC is less affluent than face-to-face communication. In implementing WFH, even after the pandemic, it is necessary to pay attention to the needs of organizations and employees and the main factors of successful WFH implementation so that WFH can be as effective as working in an office.